2018
DOI: 10.3889/oamjms.2018.421
|View full text |Cite
|
Sign up to set email alerts
|

Procalcitonin Level in Non-Small Cell Lung Cancer Patients among Indonesian Population

Abstract: BACKGROUND:Serum Procalcitonin (PCT) is a biomarker that is frequently used to diagnose an infection. In some cases of thoracic malignancy, procalcitonin level appears to increase. However, the role of procalcitonin to diagnose malignancy is not certain yet, and the causes have not been known.AIM:This study aimed to investigate procalcitonin levels in non-small cell lung cancer patients.METHODS:This was an observational study with a cross-sectional design. All lung cancer patients did not diagnose based on cyt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
14
0
2

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 16 publications
(18 citation statements)
references
References 17 publications
2
14
0
2
Order By: Relevance
“…This difference is closely related to the development of LC in patients with IPF, as the majority (73.3%) of IPF patients developed LC 18.6 ± 15.8 months after the initial diagnosis of their IPF. Our finding is in agreement with many reports that observed that PCT can be elevated due to malignancy [11][12][13][14][21][22]. Ghillani et al found increased calcitonin precursor levels as compared to healthy subjects in 17.5%, 53%, and 29% of patients with squamous cell cancer, large cell cancer, and adenocarcinoma, respectively [21].…”
Section: Discussionsupporting
confidence: 93%
See 2 more Smart Citations
“…This difference is closely related to the development of LC in patients with IPF, as the majority (73.3%) of IPF patients developed LC 18.6 ± 15.8 months after the initial diagnosis of their IPF. Our finding is in agreement with many reports that observed that PCT can be elevated due to malignancy [11][12][13][14][21][22]. Ghillani et al found increased calcitonin precursor levels as compared to healthy subjects in 17.5%, 53%, and 29% of patients with squamous cell cancer, large cell cancer, and adenocarcinoma, respectively [21].…”
Section: Discussionsupporting
confidence: 93%
“…This is the first study that compares the serum levels of the commonly used marker procalcitonin between patients with IPF and those with combined LC-IPF. Previous reports had addressed levels of PCT either in acute exacerbations of interstitial lung disease [ 10 ] or LC alone [ 11 - 13 ], with mixed results. In the current study, we had chosen well-characterized groups of stable IPF alone and LC-IPF patients who had no known factors compromising the evaluation of PCT levels (i.e., infectious, inflammatory, or therapy-induced factors).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This is in line with Soeroso et al that found the most common NSCLC was adenocarcinoma (80.9%). 15 Along with the course of disease, chemotherapy also increases hypercoagulable state risk, depending on duration and particular agents. Platinum-based chemotherapy, anthracyclines, and nitrogen mustard analogs have an association with venous thromboembolism (VTE) state in various solid tumor malignancy.…”
Section: Discussionmentioning
confidence: 99%
“…Through the analysis of keywords, the current research hotspots in the field of respiratory diseases appear to be sepsis, pneumonia, and infections. However, according to indepth analysis of the literature, increasingly, more and more studies are examining the relationship between PCT and other diseases of the respiratory system, such as the value of PCT in the diagnosis and prognosis of lung cancer patients (10,11,(21)(22)(23)(24). Studies have shown that even if patients with lung cancer are not co-infected, the average serum PCT levels were higher than that of non-infected patients without lung cancer, and the higher the PCT levels, the worse the prognosis (10,22,23).…”
Section: Discussionmentioning
confidence: 99%